VD_FINDINFO HC / 2012 / 32 vom 23. November 2011 - VD Tribunal cantonal (2011)
DÉPENS, RÉPARTITION DES FRAIS | 106 al. 1 CPC (CH), 106 al. 2 CPC (CH), 107 al. 1 let. a CPC (CH), 110 CPC (CH), 319 let. b ch. 1 CPC (CH), 322 al. 1 CPC (CH)